Analisa Pengaruh Penyakit Mulut dan Kuku terhadap Angka Kelahiran dan Kematian Pedet Sapi Aceh di Kecamatan Darul Hasanah Kabupaten Aceh Tenggara - Kartono, Kartono; Assauwab, Muhammad Husaini (UNIVERSITAS LABUHANBATU, 2023)
The purpose of this research is to determine the impact of Foot and Mouth Disease (PMK) on the birth and mortality rates of Aceh cattle calves in the Darul Hasanah subdistrict of Aceh Tenggara Regency. The study also aims to identify the factors that influence the spread of PMK in the region and to investigate strategies for its control. The research was conducted over a period of four months, from January to April 2023, in the Darul Hasanah subdistrict of Aceh Tenggara Regency. A purposive sampling method was used to select high-population villages with cases of PMK in Aceh cattle. The results of the study indicate that PMK has a significant impact on the birth and mortality rates of Aceh cattle calves in the Darul Hasanah subdistrict.Â Keywords: Bos indicus, Local, Management, Farmers, PMKÂ